2020
DOI: 10.3390/healthcare8040477
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Myopic Astigmatism with Topography-Guided Laser In Situ Keratomileusis (TOPOLINK)

Abstract: We aim to assess the feasibility of topography-guided laser in situ keratomileusis (TOPOLINK) for correcting pre-existing and surgical-induced astigmatism. A retrospective, single center cohort study was conducted. Patients with pre-existing irregular myopic astigmatism were recruited into the primary group and those with irregular myopic astigmatism following laser in situ keratomileusis (LASIK) were recruited into the enhancement group. The changes in uncorrected visual acuity (UCVA), best-corrected visual a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Currently, the exact association of varied intensity PA (light, moderate, or vigorous) and sedentary behaviors with refractive errors is still unclear. Studies have found that astigmatism is known to lead to amblyopia or myopia [22,23]. It has been shown that playing video games and computer use may increase the risk of astigmatism [24].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the exact association of varied intensity PA (light, moderate, or vigorous) and sedentary behaviors with refractive errors is still unclear. Studies have found that astigmatism is known to lead to amblyopia or myopia [22,23]. It has been shown that playing video games and computer use may increase the risk of astigmatism [24].…”
Section: Introductionmentioning
confidence: 99%